Designing Prison-Based Parenting Programs to Maximize Their Outcomes. (May 2019) - Butler, Michelle; Percy, Andrew; Hayes, David; Devaney, John
Parenting programs are increasingly being offered in prison as governments seek to reduce the negative consequences of parental imprisonment and encourage desistance from crime. However, little is known about the design and delivery of such programs and how this may shape program effectiveness. This article seeks to address this gap by examining how the design and delivery of the Families Matter program for imprisoned adult fathers in Northern Ireland affected its ability to achieve its goals of improving family relationships and fathers' parenting skills. Examples of good practice are offered, as well as challenges that remain to be overcome. It is argued that more attention needs to be paid to the design and delivery of these programs if their ability to achieve long-term improvements in family relationships and parenting skills are to be improved.